Análisis empírico de las diferancias de eficiencia entre las empresas familiares y las no familiares - A. I. García de la Borbolla Fernández; J. Herrera Madue\~no; M. Larrán Jorge; G. Sánchez Gardey; A. Suárez Llorens (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
This paper analyses differences of efficiency between family and non family controlled firms. To measure efficiency three subrogate variables have been defined (financial profitability, economic profitability and margin profitability). The empirical study, developed on a sample of 765 andalusian firms do not verify any of the hypothesis extracted from Agency and Transaction Costs theories. On the other hand, data show clearly that family ownership and efficiency are independent variables.
Keywords: 330; family businesses; differential factors; efficiency; agency and transaction costs theories